Pendidikan Antikorupsi Sebagai Pendidikan Karakter Bagi Peserta Didik Di Madrasah - Abdul Aziz (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
Corruption is a form of dishonesty or criminal act committed by a person or an organization entrusted with a position of power, to obtain illicit profits or abuse of power for one's personal gain. Corruption can involve a wide range of activities including bribery, influence peddling and embezzlement and may also involve practices that are legal in many countries. Political corruption occurs when officials or other government employees act in an official capacity for personal gain. Corruption is most common in kleptocracy, oligarchy, drug-state, and mafia state. Corruption and crime are endemic sociological events that occur with regular frequency in almost all countries on a global scale in varying degrees and proportions. The latest data shows that corruption is on the rise. Each country allocates domestic resources for the control and regulation of corruption and crime prevention. The strategies undertaken in order to fight corruption are often summarized in the term anti-corruption. In addition, global initiatives such as the United Nations Sustainable Development Goals also have targets that are expected to substantially reduce corruption in all its forms.